"كيمياء الخطاب القرآني في سورة الإخلاص" - قراءة في إعادة إنتاج الدّلالة من تفاعل العناصر اللّسانيّة- (مجلة إحالات, 2025)
قد يجد الباحث اللّساني في المقاربة الكيميائيّة،أداةً لسانيّة حديثة،فعّالة في المعالجة التأويليّة للخطاب القرآني،بما توافر لها من العناصر اللّسانيّة،في مادّته اللّغويّة المتفاعلة،ابتداءً من مستواها الأفقي،الذي تمثله الوظيفة الاتّساقيّة لتلك العناصر اللّسانيّة،إلى المستوى الشّاقولي،الذي يتمظهر في الوظيفة الدّلاليّة،والّذي يخصّ دلالات البنية اللّسانيّة للمادّة القرآنيّة،ومن ورائها الخطاب القرآني،والذي يجاوز إحداثيات التنزيل الأوّل،التي جادت به مصنفات التفسير الكلاسيكي،إلى تأويلية الخطاب القرآني،بما يوافق تطوّر العلم الحديث،ويواكبه مواكبة سلسة. هذا؛وإنّ استثمار المباحث اللسانية،بالمنهج العلمي الكيميائي،في الدّرس التّأويلي للخطاب القرآني، الكلاسيكي،ومنه ما جاء في قصار السّور،التي تتصل على الغلبة منها بالعهد المكّي،يمكّن المشتغلين بالدّرس التفسيري،في حلّته الجديدة،ومن ورائه الدّرس اللّساني العربي الحديث،وذلك للارتباط الأنثروبولوجي بينهما،في بدايات الدّرسين القديمين،وما يمثّله الأوّل في الثاني من الحث العلمي عليه،والدافع إليه،لاسيما وأنّه يتعلّق بالمدوّنة القرآنيّة المثالية المقدّسة،من الوقوف على ظواهر تأويليّة حديثة،بما تفرز الظّواهر اللّسانيّة للمباني العربيّة،المبثوثة في المادّة القرآنيّة،وبما تنتجه المدنيّة العلميّة الحديثة،من تضامّ العلوم الإنسانيّة عامّةً،والدّقيقة خاصّةً،لاسيما وأنّ اللّسانيّات من جملة العلوم الدّقيقة،وما تفرزه من نظريّات قريبة من الدّقّة،وهي تحاول أن تفسّر لما استعصى تأويله،في الدّرس الفيلولجي؛من ذاك المباحث الكيميائيّة في تفاعل العناصر الكيميائيّة،الّتي تمكن فلسفتها،في موضع مقاربة إجرائيّة لسانيّة،تعمد المدوّنة القرآنية مصدرا لها،على غير ما هو معكوس،في اعتمادها موضع تطبيق للنظريات البشريّة القاصرة،على ما هو مثالي مقدّس.Abstract:The linguistic researcher can find in the chemical approach a modern linguistic tool, effective to interpret the Quranic discourse, with its linguistic elements, in its interactive linguistic material, from its horizontal level, represented by the coherent function of these linguistic elements, up to the vertical level, In the semantic function, which is related to the meanings of the linguistic structure of the Quranic material, and the Qur'anic discoursebehind, which goes beyond the first coordinates of the first download, in which the classical interpretation works were attributed to the interpretation of the Quranic speech, continuewith its smooth.It is because the investment of the field linguistics research, in the scientific and chemical method, in the lesson of interpretation of the Quranic and classical discourse, and of what is stated in the short chapters of Sura, which relate to the predominance of the mecca alliance, because of the anthropological link that unites them, at the beginning of the two oldlessons, and what the first represents in the second scientific impulse, and the motivation that motivates it, especially as regards the Holy Quranic Code of the Holy, to take a stand on phenomena of modern interpretation, including the linguistic phenomena of Arab buildings,In the coranic article and in modern scientific civilization, the harmony of the human sciences in general, and especially the minute, especially as the linguistics between refined sciences and theories close to precision, seeking to explain why interpreting the interpretation, chemical detective in the interaction of chemical elements, which allow its philosophy, in the position of a procedural approach to linguistics, the Qur'anic code is asource, contrary to what is reversed, in the adoption of the application of deficient human theories, which is ideally sacred.